Crossing the River - Pedersen, Miriam Aurora Hammeren, 1990- (Book collections on Project MUSE., 2019)
What do you do when you realize that one of your most fundamental ideas about yourself is actually false? How do you resituate yourself in a world that has been turned upside down? This book charts the early stage of the author's journey of gender transition, as well as her process of settling down in South Africa as a fledgling academic. The story is a deeply personal one, but also one that will resonate with other transgender people, migrants, academic hopefuls, and border-crossers of all kinds. As a story of coming to terms with an identity in flux, it illustrates the fundamental open-endedness of all human identities.